An investigation of spelling skills in Turkish: the role of phonological encoding and rapid naming in the literacy skills of third and fourth graders - Sönmez, Ecehan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2015., 2015)
The present study investigated the role of phonological encoding (PE) skills and rapid automatized naming (RAN) in predicting reading and spelling achievement of Turkish-speaking children. It compared the underlying processes of spelling with those involved in reading with reference to developmental differences across grade levels and the transparent orthography of Turkish. Besides, it explored variations in the spelling errors found in the students’ handwritings in word and text level spelling based on grade levels and task modality (copying vs. dictation). The participants were 77 students attending Grade 3 and Grade 4. A number of literacy tests were used to collect data, and the data were analyzed both quantitatively and qualitatively. Although the fourth graders had similar levels of PE skills with the third graders, they performed significantly better in RAN, word reading and word spelling tests. Regression results showed that RAN was a strong precursor of reading while PE was a significant predictor of spelling in Turkish. Still, RAN made significant contributions to spelling skills beyond PE at both grade levels. In addition, PE significantly contributed to the reading skills of the third graders while it did not account for significant amounts of variance in the reading skills of the fourth graders. As the grade level increased, the effect of phonological knowledge tended to decrease whereas automatization gained more importance in predicting reading and spelling performance. The results of the error analysis revealed some variations in the error patterns across modalities, but no striking differences were found across grade levels.
Keywords: Turkish languag -- Phonology.; Speed reading.